2019
DOI: 10.1038/s41598-019-49959-4
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Plasma-Catalytic System with Rang 19pr Catalyst for Conversion of Tar

Abstract: A coupled plasma-catalytic system (CPCS) for the conversion of toluene was investigated and compared to the homogeneous system of gliding discharge plasma. Toluene was used as a model compound, which is present in tars. The study was carried out at atmospheric pressure, in a gas composition similar to the one obtained during pyrolysis of biomass. The effect of the initial toluene concentration, energy supplied to gliding discharge (GD) and the presence of a catalyst on the conversion of toluene was studied. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…Balances are in line at 90–98%, which shows that nearly all of the products generated during the process have been quantified. The mechanism of the process has already been described …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balances are in line at 90–98%, which shows that nearly all of the products generated during the process have been quantified. The mechanism of the process has already been described …”
Section: Resultsmentioning
confidence: 99%
“…A homogeneous nonthermal plasma and a plasma-catalytic system have been widely used for many environmental technologies. The plasma conversion of toluene is investigated by many research groups all over the world. In the coupled plasma-catalytic system, high conversion of toluene and other volatile organic compounds (VOCs) was obtained and the activity of the catalyst was stable. , This may suggest that the use of active catalysts operating in the plasma of gliding discharge can be successfully implemented to obtain higher conversions of tars. Based on the previous experiments conducted in the plasma-catalytic system with nickel as a catalyst, it can be concluded that nickel on the catalyst surface influenced the tar decomposition process. , The purpose of this work was to investigate the effects of the power of discharge, initial concentration of toluene, and the presence of G-0117 catalyst on the conversion of C 7 H 8 and the composition of outlet gas, as well as its calorific value. The goal of the research was to determine the durability of the catalyst activity during a process lasting approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various plasma-catalytic systems are used. A catalyst may be located in a plasma zone [1][2][3][4][5][6][7], an electrode may be the catalyst [8,9], and often the catalyst is located outside the plasma zone [1,[10][11][12][13][14][15][16][17][18]. This way of placing the catalyst prevents the destruction of the catalyst by plasma and the disturbance of the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for the A3 series, as the discharge power increases, the conversion of toluene decreases by about 5% (Figure 5). This may be due to the lower concentration of hydrogen radicals generated in plasma (compared to the gas B3), which are involved in the activation reaction of toluene in the catalytic process [16]. Moreover, the values of toluene conversion obtained in the plasma-catalytic system are higher than in the homogeneous system [10] throughout the investigated range of initial toluene concentration.…”
Section: Plasma-catalytic Conversion Of Toluenementioning
confidence: 99%